Analisis Penerapan Administrasi Digital pada PT Semesta Integrasi Digital - Raihan Nurrohman; Christian Wiradendi Wolor; Adnan Kasofi (Politeknik Kampar, 2025)
This study applies a qualitative descriptive method with the aim of describing and analyzing the issues found. This qualitative approach is based on the collection of primary and secondary data. Primary data in this study were obtained through observation, interviews, and documentation, while secondary data were obtained through books, previous research, and articles relevant to this study. The data source in this study was interview transcripts obtained from a number of respondents called research informants. The informants were selected based on a certain method because their abilities or positions were considered to be able to describe the problems that would be the object of the study. The informants in this study numbered four people consisting of two operational heads and two administrative staff. The main objective of this study was to understand the implementation of digital administration at PT Semesta Integrasi Digital, including the challenges faced in implementing digital administration, and the digital administration data security system of PT Semesta Integrasi Digital. The results of the study showed that the implementation of digital administration at PT Semesta Integrasi Digital has increased work efficiency, especially in terms of data management and reporting. This finding is reinforced by the results of interviews which showed that when the data security system has been implemented using encryption and access restrictions, there are still challenges in terms of further data integration and protection.